Ebu’l Hasan Harakânî’ye Göre Sûfi Benlik Dönüşümü / Transmutation of the Self according to Ebu’l-Hasan al-Harakânî - Işıtan, İbrahim (Journal of History Culture and Art Research, 2013)
Abstract Sufi psychology is a new area of research dealing with the attitude and the behavior of the sufis. While studying the developments of human psychology focusing on human attitudes and behavior as well as their origins in the human body, we had the opportunity to study those of the sufi from a psychological perspective. When it comes to modern psychology, we studied the integrity of the self, also known as 'self realization’ by observing the characteristics of someone who has attained a certain degree of perfection, in addition to this we have worked on certain methods and theories pertaining to the development of the personality. Sufism has built its own theory of the personality based on its own methods which aim at studying the basic characteristics of the spiritual evolution of the human being. Modern psychology also examines pathological human behavior and comes up with adequate therapies so as to readjust these behaviors accordingly. Likewise, sufism has an interest in inadequate human behavior in the words of sufism 'the vices of the soul’ it also aims at readjusting these types of behavior but from a spiritual point of view. In these writings, we will be studying the transmutation of the sufi self according to the classical era sufi Ebu’l-Hasan al-Harakânî and we will examine the two aspects of that transmutation: the psychological one and the psycho-spiritual one. Öz Sûfî psikolojisi, mutasavvıfların tutum ve davranışlarını inceleme konusu yapan çok yeni bir araştırma alanıdır. İnsan tutum ve davranışlarını ve bunların kaynağını araştıran psikoloji biliminin gelişmesi, sûfi literatüre de psikolojik açıdan bakma imkânı sağlamıştır. Psikolojide kendini gerçekleştirme kavramıyla ifade edilen benlik bütünlüğü konusu araştırılmış, söz konusu bu bütünlüğü sağlayan üstün kişilerin temel özellikleri incelenmiş ve kişisel gelişim konularında kayda değer bir takım yöntemler ortaya konmuştur. Sûfî anlayış da kendine has metotlarla bir benlik gelişimi teorisi oluşturmuş, seyri sülûk diye adlandırılan rûhî gelişimin temel karakteristiklerini ortaya koymuştur. Modern psikoloji insanın davranışını ve davranışlarındaki patolojik durumları anlamaya ve yeniden düzenlemek için terapi yöntemleri geliştirmeye çalışırken, sûfî hayat biçimi de insanı anlamaya ve olumsuz ve patolojik diye nitelendirebileceğimiz davranışlarını tasavvuf diliyle ifade edersek nefsin ayıplarını rûhî ve mânevi yapıya göre yeniden düzene koyma konusu üzerine durmuştur. Bu çalışmada, sûfî benlik dönüşümü konusu, klasik dönemin ünlü sûfilerinden olan Ebu’l Hasan Harakânî’ye göre incelenmiş ve sûfî benlik dönüşümün fizyolojik ve psiko-ruhsal boyutlardaki yansımaları kısaca ele alınmıştır. La Transmutation de Soi selon Ebu’l-Hasan al-Harakânî Résumé La psychologie soufie est un nouveau domaine de recherche qui étudie les attitudes et comportements des soufis. En parallèle du développement de la psychologie moderne qui étudie les attitudes et comportements humains et leurs origines dans l’organisme de l’homme, on a eu l’occasion d’étudier les attitudes et comportements des soufis selon le point de vue psychologique. En psychologie moderne, on a étudié le sujet de l’intégrité de soi appelé par l’expression de 'réalisation de soi’ en examinant les principales caractéristiques des personnes dites 'perfectionnées’ et on a développé certaines méthodes et théories au sujet du développement de la personnalité. La vie soufie a développé une théorie de la personnalité selon ses propres méthodes en étudiant les caractéristiques de base de l’évolution spirituelle de l’homme. La psychologie moderne examine aussi les comportements pathologiques et développe des thérapies adéquates pour réadapter les comportements humaines et de même le soufisme s’intéresse aux comportements inadéquats de l’homme autrement dit les vices de l’âme humaine selon l’expression des soufis dans l’idée de réadapter ces comportements selon la vision spirituelle. Dans notre travail, nous allons étudier la transmutation de soi soufi selon le soufi de l’âge classique Ebu’l-Hasan al-Harakânî et examiner les deux dimensions de la transmutation de soi soufi : transmutation au niveau physiologique et celle au niveau psycho-spirituel.